The Influence Of Weather On Aviation Traffic Performance Aerodrome Control Tower During The Rainy Season At JATSC - Fahmi Sohih Badilah; Dwi Lestary; Elfi Amir (CV. AFDIFAL MAJU BERKAH, 2026)
Weather conditions are one of the external factors that significantly affect air traffic performance, particularly during the rainy season in tropical regions such as Indonesia. This study aims to analyze the effect of weather parameters on air traffic performance during the rainy season at Jakarta Air Traffic Services Center (JATSC) and to identify which weather parameters have the most significant impact on flight operations. This research employed a quantitative approach with a correlational research design. Data were collected through structured questionnaires distributed to 93 respondents consisting of Air Traffic Controllers (ATC), aviation meteorologists, and airport operations managers, supported by secondary operational and meteorological data during the 2023–2024 rainy season period. The weather parameters analyzed included precipitation, visibility, wind speed and direction, cloud ceiling, lightning activity, air temperature, and relative humidity. The results indicate that visibility, precipitation intensity, lightning activity, and wind speed are the most influential weather parameters affecting air traffic performance, particularly in relation to flight delays, go-arounds, and flight cancellations. The study concludes that all weather parameters have a significant impact with varying levels of influence, highlighting the need for integrated operational management and weather mitigation strategies to enhance safety and efficiency in air traffic operations at JATSC.